Scientific Perspectives on the Development of Social Competencies in Nurses for Effective Professional Communication - Sadovei, Larisa; Tudose (Sliusari) , Adriana (Didactica Danubiensis, 2025)
Objectives: This study aims to identify the key social competencies relevant to nursing practice, emphasize their essential role in fostering effective professional communication with patients, colleagues, and interdisciplinary healthcare teams, and propose strategies for developing interpersonal skills within a patient-centered healthcare system that prioritizes empathy, active listening, and teamwork. Prior Work: The research builds on existing literature concerning emotional intelligence, social competencies, and the doctor-patient relationship. It draws upon prior studies in healthcare professional education (e.g., Goleman, 1995; Salovey & Mayer, 1997) and explores how social communication contributes to improving the quality of medical care and patient satisfaction. Approach: The study employed a thorough review of relevant literature, along with theoretical synthesis, comparative analysis, scientific reasoning, and conceptual modeling. The effectiveness of socio-emotional competency development depends largely on the clear identification and definition of the most relevant social competencies for nursing practice. Results: The findings highlight a strong interest in the development of social competencies among nurses, recognizing them as essential for optimizing professional communication with patients, fostering empathetic care, promoting effective teamwork, and enhancing satisfaction for both patients and healthcare professionals. Implications: These results can contribute to the enhancement of professional training programs in medical education and support decision-making processes among trainers, medical institution administrators, and university faculty responsible for post-secondary and university curricula development. Additionally, the study provides a solid foundation for further research in medical pedagogy. Research Value: The study underscores the role of social competencies in the professional formation of nurses by emphasizing the importance of effective professional communication, thereby contributing to the expansion of scientific knowledge in the field of nurse-patient and interprofessional communication.